The Effect of Modular Building Model Learning Media and Student Skills on Learning Outcomes Construction and Property Business Expertise Program at Siwa Lima Vocational School, St Yosep Langgur - Namsa, Yohanis Paulus; Daud, Metsi; Oroh, Rolly Robert; Rompas, Parabelem Tino Dolf (International Journal of Information Technology and Education, 2023)
Is there any influence of the modular building model learning media and student skills on student learning outcomes at Siwa Lima St Yosep Langgur High School is a question that is the aim of this research. This study used quantitative methods by collecting data using questionnaires, documentation and tests while analyzing data using multiple regression analysis with the help of the SPSS 24 program. The results showed that there was a positive and significant relationship between the Modular Building Model Learning Media and Student Skills on the Learning Outcomes of the Construction and Property Business Skills Program at Siwa Lima St. 1 .67943 t table so Ho is rejected and Ha is accepted, meaning that the more creative the learning media used, the higher the student learning outcomes, there is a positive and significant relationship between student practice and Learning Outcomes of the Construction and Property Business Skills Program at Siwa Lima High School St Yosep Langgur with a t value of the practice intensity variable ( X 2 ) 6.381 ≥ 1 .67943 t table so Ho is rejected and Ha is accepted meaning that the higher the student's practice, the higher the student learning outcomes, there is a positive and significant relationship between Learning Media Modular Building Models and Student Skills Against Learning Outcomes in the Construction and Property Business Skills Program in SMA Siwa Lima St Yosep Langgur and the contribution of the variable Learning Media Modular Building Models and Student Skills to Learning Outcomes of the Construction and Property Business Expertise Program at SMA Siwa Lima St Yosep Langgur is 89.7%, while the rest is influenced by other variables that do not become study in research.